1999
DOI: 10.2307/3870749
|View full text |Cite|
|
Sign up to set email alerts
|

Elevated Glutathione Biosynthetic Capacity in the Chloroplasts of Transgenic Tobacco Plants Paradoxically Causes Increased Oxidative Stress

Abstract: Glutathione (GSH), a major antioxidant in most aerobic organisms, is perceived to be particularly important in plant chloroplasts because it helps to protect the photosynthetic apparatus from oxidative damage. In transgenic tobacco plants overexpressing a chloroplast-targeted gamma-glutamylcysteine synthetase (gamma-ECS), foliar levels of GSH were raised threefold. Paradoxically, increased GSH biosynthetic capacity in the chloroplast resulted in greatly enhanced oxidative stress, which was manifested as light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 42 publications
4
64
0
Order By: Relevance
“…The present results are also consistent with those obtained with transgenic poplars overexpressing cEC synthetase since these transformants contained increased levels of GSH and were better protected from paraquat-induced oxidative stress. In contrast, Creissen et al (1999) very recently reported that tobacco plants overexpressing a chloroplast targeted cEC synthetase and containing increased foliar pools of both GSH and cEC suered from greatly enhanced oxidative stress, which was manifested as light-intensitydependent chlorosis or necrosis. These authors did not detect increased GR activity in these transformants whereas it was clearly demonstrated here that the levels of GR activity changed with GSH contents.…”
Section: Discussionmentioning
confidence: 93%
“…The present results are also consistent with those obtained with transgenic poplars overexpressing cEC synthetase since these transformants contained increased levels of GSH and were better protected from paraquat-induced oxidative stress. In contrast, Creissen et al (1999) very recently reported that tobacco plants overexpressing a chloroplast targeted cEC synthetase and containing increased foliar pools of both GSH and cEC suered from greatly enhanced oxidative stress, which was manifested as light-intensitydependent chlorosis or necrosis. These authors did not detect increased GR activity in these transformants whereas it was clearly demonstrated here that the levels of GR activity changed with GSH contents.…”
Section: Discussionmentioning
confidence: 93%
“…1 O 2 -specific signaling pathways also have been described for mammals (20)(21)(22)(23), Chlamydomonas (24), and the phototrophic bacterium Rhodobacter sphaeroides, in which the alternative sigma factor, sigma(E), is essential for activating a specific transcriptional response to 1 ) that was expected to enhance primarily 1 O 2 production were more resistant if they were pretreated with high concentrations of exogenous H 2 O 2 2 h before the beginning of high light stress, as indicated by a reduction of photoinhibition and the absence of visible damages of the leaves (26). It is tempting to speculate that in this case, similar to what has been reported in our present work, H 2 O 2 protects photosynthetic membranes by modulating the signaling of 1 O 2 that is generated during high light stress.…”
Section: Discussionmentioning
confidence: 95%
“…The increase in the redox status of ascorbate in DHAR-overexpressing plants might have been perceived as a stress to which the plant responds by increasing antioxidant concentration. Tobacco engineered to overexpress ␥-ECS contained elevated glutathione levels but, paradoxically, exhibited chlorosis and necrosis (34). However, these growth defects were not correlated with the increase in glutathione but rather with a decrease in glutathione redox state.…”
Section: Discussionmentioning
confidence: 99%
“…Such a response was provoked in tobacco engineered to overexpress chloroplast-targeted ␥-glutamylcysteine synthetase (␥-ECS), which resulted in increases in glutathione (32). However, DHAR-overexpressing plants did not exhibit any visible oxidative stress symptoms as were observed in ␥-ECSoverexpressing plants (34). Moreover, no significant change in the activity of GR, APX, CAT, and SOD was detected, with the exception of a 10-25% decrease in SOD activity in mature and presenescent leaves (P Ͻ 0.05; Fig.…”
Section: Increased Dhar Activity Increases Asa and Glutathione Contenmentioning
confidence: 99%